Building Islamic Financial Literacy in Papua: Opportunities and Challenges - Hasbiah Hasbiah; Nanda Yuda Putri Aisyah; Karfin Karfin; Raihana Hasni Ladaku; Sri Prilmayanti Awaluddin (PT Mattawang Mediatama Solution, 2025)
Islamic financial literacy is a crucial foundation for promoting inclusive and equitable economic growth, particularly in Eastern Indonesia, including Papua. Low literacy levels, limited access to Islamic financial institutions, and insufficient understanding of Islamic economic principles present significant challenges for developing a robust Sharia-based financial system in the region. This study aims to analyze the current state of Islamic financial literacy in Papua, identify development opportunities, and evaluate challenges from social, cultural, infrastructural, and institutional perspectives. A descriptive qualitative approach was employed, reviewing literature, reports from the Financial Services Authority (OJK), Bank Indonesia, the Central Statistics Agency (BPS), and relevant academic studies. The analysis focused on socio-cultural, economic, institutional, and digital technology aspects. The results indicate that Islamic financial literacy in Papua remains low, especially in remote areas, but significant opportunities exist through digitalization, strengthening local financial institutions, leveraging educational institutions, and multi-stakeholder collaboration. Community-based approaches that integrate local wisdom, such as the values of mutual cooperation and deliberation, are effective in increasing understanding and acceptance of Sharia financial principles. In conclusion, enhancing Islamic financial literacy in Papua not only improves financial inclusion but also fosters an ethical, sustainable, and equitable economic ecosystem, supporting socio-economic transformation based on Islamic values.